SCREENING OF DIFFERENT SOLVENT EXTRACTS FOR ANTIFUNGAL ACTIVITY OF SEEDS OF PSORALEA CORYLIFOLIA L. AGAINST IMPORTANT SEED BORNE ASPERGILLUS SPECIES OF MAIZE (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Petroleum ether extract of seeds of Psoralea corylifolia was recorded a maximum antifungal activity in Aspergillus flavus oryzae (93.5%) and A. tamarii (92.43%); Benzene extract recorded a maximum inhibition in A. niger (88.10%), A. flavus oryzae (83.80%) and A. tamarii (81.10%). In chloroform extract A. tamarii recorded 74.60% and A. niger showed 74.16% inhibition. In methanol extract A. tamarii and A. flavus oryzae recorded 69.50% and in ethanol extract A. flavus oryzae showed 74.63% and A. flavus recorded 67.10% inhibition in 2.0% concentration of extract. Compared to synthetic fungicides Captan and Thiram, Captan recorded 85.0% to 95.0% inhibition and Thiram showed 100% inhibition against all the test fungi. Among the three different fractions I, II and III, Fraction II showed a significant activity against all test fungi compared to fraction I and fraction III.